1997
DOI: 10.3758/bf03211292
|View full text |Cite
|
Sign up to set email alerts
|

A mere exposure effect for transformed three-dimensional objects: Effects of reflection, size, or color changes on affect and recognition

Abstract: If the mere exposure effect is based on implicit memory, recognition and affect judgments should be dissociated by experimental variables in the same manner as other explicit and implicit measures. Consistent with results from recognition and picture naming or object decision priming tasks (e.g., Biederman & E.E. Cooper, 1991, 1992; L.A. Cooper, Schacter, Ballesteros, & Moore, 1992), the present research showed that recognition memory but not affective preference was impaired by reflection or size transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
73
4

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 59 publications
9
73
4
Order By: Relevance
“…A similar dissociation has been reported with the affect and recognition tasks. Seamon et al (1997) have shown that recognition, not affective preference, was impaired by reflection or size transformations of visual objects between study and test, much in the same way as timbre change was found to impair recognition but not likingjudgments.…”
Section: Discussionmentioning
confidence: 92%
“…A similar dissociation has been reported with the affect and recognition tasks. Seamon et al (1997) have shown that recognition, not affective preference, was impaired by reflection or size transformations of visual objects between study and test, much in the same way as timbre change was found to impair recognition but not likingjudgments.…”
Section: Discussionmentioning
confidence: 92%
“…Each study stimulus was presented at the center of the screen for 2500 ms, followed by a 3500 ms interval (see Seamon et al, 1995Seamon et al, , 1997, for a similar procedure).…”
Section: Incident Study Phasementioning
confidence: 99%
“…Nonetheless, earlier findings showed that, even when a feeling of fluency might be expected, some fluently processed stimuli may continue to elicit an explicit preference, such as after an obvious supraliminal presentation phase, of the kind that has been used in some mere exposure paradigms (e.g., Seamon et al, 1995Seamon et al, , 1997. Consequently, the nature of the connection between ease of processing and explicit preference judgments and the importance of additional indirect factors such as expectations and attributions of perceived fluency seem to be complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this link between repetition priming and mere exposure is intuitively appealing, not least because of the opportunity it accords to accommodate the latter within an established theoretical framework (e.g., Roediger, Weldon, & Challis, 1989;Tulving & Schacter, 1990), there have been few attempts to explore it directly. Seamon and colleagues (1995;Seamon et al, 1997) have made some progress in this respect, reporting a number of parallels between mere exposure and repetition priming. For example, Seamon et al (1997) found that study-to-test changes in retinal size and left-right orientation produced the same pattern of results using a mere exposure task, as had been previously reported with an object decision task (Cooper, Schacter, Ballesteros, & Moore, 1992).…”
mentioning
confidence: 99%